A consolidação do setor farmacêutico na economia global: crescimento, influência, desvios e marketing - Stacciarini, João Henrique Santana (2023)
This study investigates how the pharmaceutical sector has become one of the largest and most influential economic sectors of our time. It presents figures and information that support this claim and aims to elucidate the factors that contributed to such a rise. Since Alexander Fleming's discovery of penicillin in 1928, pharmaceutical industries have evolved from small entities - often family-owned and operating locally - to multinational corporations valued at hundreds of billions of dollars with global influence. However, beyond the discovery and diversification of drugs, increased demand, and expansion of production capacity, part of this evolution is underpinned by complex, and in some cases perverse, strategies prioritizing profit maximization over public and individual health. The findings of this study reveal that, over the past two decades, the sector's revenues have quadrupled, reaching $1.48 trillion in 2022, an amount comparable to the Gross Domestic Product (GDP) of developed countries such as Spain. The twenty largest companies in the sector have a combined market value of $3.5 trillion and assets totaling $1.86 trillion, generating annual revenues of $820 billion and profits of $181.6 billion. For context, the assets of these companies alone are comparable to the GDP of all Sub-Saharan African countries. Companies, like Johnson & Johnson, have a market value exceeding the GDP of 184 nations. The study also examines and discusses questionable practices adopted by the pharmaceutical industry, including investing billions in lobbying and election financing, influencing regulatory agencies, financially supporting patient organizations, sponsoring authors of "Clinical Guidelines", manipulating and concealing drug research and tests, and directing massive investments to strengthen ties with prescribers, university hospitals, and academic institutions. Concrete examples of these actions are provided, backed by studies, data surveys, and court decisions, underscoring the alarming consequences of this reality. Lastly, the research analyzes pharmaceutical marketing as a primary sales boost strategy. Despite drugs not being ordinary commodities, susceptible to promotion under the lens of rampant consumption, companies invest billions annually in directto-consumer advertising. In the Brazilian context, the pharmaceutical sector stands out as one of the main investors in marketing. In recent years, several companies in the field have ranked among the highest individual advertising spenders. The emergence of digital marketing strategies driven by the internet, advanced algorithms, and social networks, combined with advertising campaigns harmful to public and collective health, underscore a concerning and challenging scenario.